2019
DOI: 10.1088/1755-1315/276/1/012061
|View full text |Cite
|
Sign up to set email alerts
|

Amplification and Analysis of Rbcl Gene (Ribulose-1,5-Bisphosphate Carboxylase) of Clove in Ternate Island

Abstract: DNA Barcoding is recommended as a tool for identifying and confirming species within the taxonomy framework. The rbcL gene is the barcode DNA for plant species. Ternate Island is one of clove plantation center in North Maluku. The diversity and productivity of cloves on the Ternate island known since in earlier times. This study has a purpose to amplify the rbcL gene in clove plants collected from clove plantations of communities in Ternate island. Isolation of total DNA carried out with using ZymoBiomic (Zymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…PCR reaction was performed with the primers rbcL. The results showed that 35 samples of Huperzia were a single-form band with the size of 650 bp (Figure 1), which was a resemblance to the report of Sundary and Papuangan [22] who applied the rbcL gene for analysing of Syzygium aromaticum.…”
Section: Molecular Markers Application To Identify Huperzia Samples Bsupporting
confidence: 69%
See 3 more Smart Citations
“…PCR reaction was performed with the primers rbcL. The results showed that 35 samples of Huperzia were a single-form band with the size of 650 bp (Figure 1), which was a resemblance to the report of Sundary and Papuangan [22] who applied the rbcL gene for analysing of Syzygium aromaticum.…”
Section: Molecular Markers Application To Identify Huperzia Samples Bsupporting
confidence: 69%
“…Among them, there was only one sample (BK3) belonging to H.phlegmarioides group, and the others of the 34 samples were clustered in H.squarrosa group, respectively (Figure 3 and Figure 4). In the fact that the available databases on the rbcL gene are very useful and facilitated to identify phylogenetic relationships of many plant species at interfamilial levels [25,22]. Dubisson [26] successfully applied rbcL sequences of 18 species of the fern genus Trichomanes for assessing their systematic relationships which showed a more accurate reflection of the generic concept applied to other fern and angiosperms.…”
Section: Ilns Volume 80mentioning
confidence: 99%
See 2 more Smart Citations
“…Maturase K ( matK (XF/5R)) and Kim matK (3F_KIM/1R_KIM), the plant plastidial gene in the chloroplast region that splices group II introns in the conserved domain X of the reverse transcriptase domain can be used as a universal DNA barcode primer for plants [ 16 ]. The chloroplast DNA sequence, ribulose–bisphosphate carboxylase ( rbcL ), is one of the universal barcode genes used in species discrimination studies due to high amplification and low mutation rate [ 17 ]. Ycf1 is the second largest gene in the plastid genome, encodes about 1800 amino acids, and is a reliable candidate for DNA barcoding [ 18 ].…”
Section: Introductionmentioning
confidence: 99%